(untitled) (Medical Forum Monthly, 2020)
Objective: To calculate the frequencies of various histopathological types of colorectal diseases and to assess the grade of the colorectal cancer. Study Design: A cross sectional observational study. Materials and Methods: 223 colorectal specimen including, biopsies and colectomy specimen were included in the study. Paraffin embedded sections were stained with routine Hematoxylin and Eosin method. The cases were diagnosed as benign or malignant and then further sub classified. Clinical records were reviewed in order to collect data regarding age, gender, clinical diagnosis and grades of tumor. H&E slides of all diagnosed cases were reviewed by two histopathologists with the aim to collect information about histological pattern and differentiation of tumor. Data was analyzed by SPSS version 23.0. Frequencies were calculated in terms of percentage. Results: Out of total (n=223) cases there were 77.1 % (n=172) benign and 22.86 % (n=51) malignant cases. Among the benign colorectal lesions 43.6% were diagnosed as Rectal polyps, 40.6 % as Colitis and 15.6 % were reported as Proctitis. As regards the microscopic variants, among 51 colorectal carcinomas, 32(62.7%) were diagnosed as adenocarcinoma, 16(31.4%) cases were mucinous-signet ring type carcinomas, 2(3.9%) were poorly cohesive and the remaining 1(2.0%) case showed cribriform pattern. Grade–I well differentiated tumors (62.7 %%) were most frequently diagnosed. Most cases of benign diseases were diagnosed between 30-40 years and malignant between 50-59 years. Both of benign and malignant colorectal pathologies showed male preponderance and mostly involved the right colon. Conclusion: Colorectal polyps were the most common benign colorectal pathologies followed by colorectal carcinoma. The great majority was observed as (grade -I) well differentiated adenocarcinoma.